Comparing the roles of inductive and capacitive coupling in a planar inductively coupled plasma through both theory and experiment - Watanabe, Masahiro, author; Collins, George J., advisor (Colorado State University. Libraries, 2001)
The inductive and capacitive excitation coil-plasma interaction in an inductively coupled plasma (ICP) is studied in this dissertation. The inductive coupling transfers power from the excitation coil to the plasma, while the parasitic capacitive coupling gives rise to rf plasma potential and DC self bias on the dielectric window, which causes unwanted dielectric window sputtering. A combined inductive/capacitive model was developed in order to quantify this problem. Prior to this work, Piejak et al. developed an air core transformer model to describe the power transfer mechanism from the excitation coil to the plasma through an inductive coupling mechanism, in which the plasma is considered the secondary circuit of an air core transformer. The plasma secondary circuit is coupled to the primary circuit through a magnetic coupling coefficient k. The inductive coupling model concludes that the power consumed in the plasma is proportional to k2 for a given rf current applied to the excitation coil. This is verified experimentally herein to determine the effectiveness of the inductive coupling model. The high rf voltage applied to drive the excitation coil creates a parasitic capacitive current pathway through the dielectric window and rf sheath to the plasma. A voltage divider circuit model is developed herein to understand the capacitive coupling from the excitation coil to the plasma, where the dielectric window and the rf sheath are considered as series capacitances. The capacitive coupling model is experimentally verified from measurements of the rf plasma potential. From both inductive and capacitive coupling models, it is shown that the rf plasma potential is indirectly influenced by inductive coupling as well as directly by capacitive coupling. Finally, a combined inductive/capacitive model is developed in order to describe fully the combined effects of the two coupling mechanisms from the excitation coil to the plasma. The combined model gives a simple relationship between the coupling and the resulting rf plasma potential variation. This combined model enables one to understand the excitation coil-plasma interaction and characterize the electrical parameters in the plasma system.
Keywords: electrical engineering; fluid dynamics; gases; plasma physics